STUDENTS’ PERSPECTIVES ON THEIR WRITING SKILLS AND THE APPLICATION OF PROCESS WRITING APPROACH IN THE ACADEMIC WRITING CLASSROOM - Ida Ayu Mela Tustiawati; I Made Yogi Marantika (Journey: Journal of English Language and Pedagogy, 2023)
This paper describes the result of student self-reflection on their writing ability and the application of the process writing approach conducted in their academic writing class. The data was collected through a self-reflection written by the participants. The students were guided to reflect on their learning experience in two aspects: their views on their writing ability and the application of the process writing approach in the classroom. Forty-four students of the English literature program from the Faculty of Foreign Languages, Mahasaraswati Denpasar University, were chosen as the participants for this study through a purposive sampling method. This method was ideal because these students have undergone similar learning experiences within the same context, which provided rich data for the study. The result of their self-reflection was analyzed using a qualitative approach. The findings indicate that more than half of the participants perceived their writing ability as lacking. Less than 10% of the participants were confident in their writing ability, and the rest saw improvement in their ability but required further practice and guidance. In terms of the application of process writing, the majority of participants agreed that it had a positive impact on their writing process.